Gas chromatography and 2D-gas chromatography for petroleum industry : the race for selectivity - Bertoncini, Fabrice; Courtiade-Tholance, Marion; Thiébaut, Didier, 1957- (Editions TECHNIP, 2013)
Detailed knowledge of petroleum products at the molecular scale has always been essential to understanding the mechanisms leading to their formation, to design thermodynamic and kinetic models employed in the refining processes, and to predict their physical properties. This book aims to provide a complete review of the implementation of gas chromatography in the oil industry, with an important focus on GCxGC and related multidimensional systems. Recent progress in the development of these chromatographic systems are discussed according to various applications. Specialists from IFP Energies nouvelles, CNRS, and major companies leading important research in this field have contributed, reporting a synthesis of the knowledge acquired from research these last fifteen years. Thus, this book will be useful for anyone involved in the separation of oil and derivatives, the student starting a research project, the academic researcher, and the refinery engineer willing to deepen their knowledge on advanced multidimensional gas chromatography, as well as molecular analysis of petroleum products.
Keywords: Gas chromatography -- Industrial applications.; Petroleum industry and trade.; elektronické knihy; electronic books